1989
DOI: 10.1038/clpt.1989.196
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamic modeling of direct suppression effects of methylprednisolone on serum cortisol and blood histamine in human subjects

Abstract: Pharmacodynamic models for "directly suppressive" effects of methylprednisolone are based on the premise that receptor interactions of steroids are followed by immediate suppression of either the circadian secretion of cortisol or the constant rate recirculation of histamine-containing basophils that persists until inhibitory concentrations of methylprednisolone disappear. Methylprednisolone doses of 0, 10, 20, and 40 mg were given as the 21-succinate sodium salt in a balanced crossover study to six normal men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…Recently pharmacodynamic models that describe the direct suppressive effects of corticosteroids have been used to characterize the response patterns of plasma cortisol concentrations, blood basophil counts (measured as whole blood histamine), and helper T lymphocyte counts after administration of methylprednisolone to young healthy male subjects. [15][16][17] These models are applied in this study to jointly examine the pharmacokinetics and pharmacodynamics of methylprednisolone in relation to gender. …”
mentioning
confidence: 99%
“…Recently pharmacodynamic models that describe the direct suppressive effects of corticosteroids have been used to characterize the response patterns of plasma cortisol concentrations, blood basophil counts (measured as whole blood histamine), and helper T lymphocyte counts after administration of methylprednisolone to young healthy male subjects. [15][16][17] These models are applied in this study to jointly examine the pharmacokinetics and pharmacodynamics of methylprednisolone in relation to gender. …”
mentioning
confidence: 99%
“…Several studies have shown that 10 to 40 mg methylprednisolone administered in the morning produce appreciable suppression of cortisol concentrations. 19,36,37 We found a similar degree of net suppression of cortisol concentrations in both phases; however, the normal circadian rhythm was significantly altered by the 4 PM dose. This dose produces nadir cortisol concentrations around the time that cortisol concentrations are normally increasing, thus perturbing the normal circadian cycle.…”
mentioning
confidence: 49%
“…Pharmacodynamic models that describe these direct suppressive effects are shown with the experimental data. 19,30 These models account for both the pharmacokinetics of the administered corticosteroid along with the suppression and return to baseline of the measured pharmacodynamic parameter.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 2 more Smart Citations